(3QSGdI aj HjGf GdeLGR hCbSGegs - (3CMeO Gdehdhjs ((3YeQ CfSi Hf GdSjO eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3bGd CSJGPfG CMeO Gdehdhi GdMeO ddg QH GdYGdejf CeG HYO agPg QSGdI ai HjGf GdeLGR hCbSGeg eJQLeI ef GdQSGdI GdaGQSjI GdJi CdagG ehdGfG GdYdGeI YUGe GdOjf s
(3BNQgG (B:s
(3Gddge ENJe dfG HGdNjQ ceG habJfG dNJe JQLeI gPg GdQSGdI GdeLGRjI GdYUGejI GdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs